Bioprospecting for a Wild Strain of Sporisorium scitamineum for the Valorization of Sugarcane Molasses into Mannosylerythritol Lipids and Cellobiose Lipids - André D. Valkenburg; Breyten van der Merwe; George M. Teke; Eugéne van Rensburg; Robert W. M. Pott (Fermentation)
Significant wastes such as bagasse, molasses, and vinasses are produced during sugarcane processing. Due to their high sugar content, these wastes are commonly used as low-cost substrates for biofuel production. However, these substrates are also suitable for the microbial synthesis of high-value biochemicals like biosurfactants. Sporisorium scitamineum, a smut fungus capable of growing on sugarcane residues and producing mannosylerythritol lipids (MELs) and cellobiose lipids (CBLs), was identified as a promising candidate for valorizing sugarcane wastes. This study investigated MEL and CBL co-production from pure sugars and sugarcane molasses using an S. scitamineum strain isolated from sugarcane residues originating from KwaZulu-Natal, South Africa. Among the sugars tested, sucrose supported the highest glycolipid production, yielding 0.24 g/L MELs and 2.73 g/L CBLs. Lower titers were achieved with fructose, and no production occurred with glucose. Sugarcane molasses also proved to be an effective substrate, yielding 1.46 g/L CBLs—the highest reported titer from an industrial waste to date. However, all titers remained far below those of other glycolipids, which consistently exceed 50 g/L. Future efforts should focus on enhancing CBL production through process optimization or genetic engineering.